REGIONAL SPECIFICS AND DIRECTIONS OF THE AGRICULTURAL PRODUCTS EXPORT IN TERMS OF THE ECONOMIC INTEGRATION - A. Zh. Bukharbayeva, (Academic Journal of Physical and Chemical Sciences, 2019)
This article reviews regional specifics of the economic integration performance and directions of the agricultural products export. It includes characteristics of distinguishing specifics of the regions, forms and types of economic integration, main principals and suggested measures on improving them in the regional aspect taking a certain rice planting region as an example.